Progress in Local Treatment of Breast Cancer: A Narrative Review - Cavalcante, Francisco Pimentel; Millen, Eduardo Camargo; Zerwes, Felipe Pereira; Novita, Guilherme Garcia (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
The present paper reports on the local treatment of breast cancer from a historical perspective. A search for articles written in English was made in the Medline and EMBASE databases, and 40 papers were selected. Over the past 10 years, various randomized, controlled clinical trials on the local treatment of breast cancer indicated that patients with the same molecular subtype may receive different individualized surgical treatments aimed at optimizing systemic adjuvant therapy. With a view to retaining the gains made in disease-free and overall survival, surgical techniques have advanced from radical surgery to conservative mastectomies, thus reducing sequelae, while adjuvant and neoadjuvant therapies have contributed toward controlling the disease, both distant metastases and local recurrence. Current studies evaluate whether future breast cancer therapy may even succeed in eliminating surgery to the breast and axilla altogether.
Keywords: breast cancer therapy; breast-conserving therapy; sentinel node biopsy; mastectomy; neoadjuvant and adjuvant therapy